Effect of floating macrophyte cover on the water quality in fishpond - Sipaúba-Tavares, Lúcia Helena [UNESP]; Fernandes de Barros, Adriana [UNESP]; De Souza Braga, Francisco Manuel [UNESP] (Universidade Estadual de Maringa, 2003)
A study was conducted during 23 days in order to evaluate the impact of floating aquatic macrophyte on the water quality of a fishpond. Water samples were collected in four points, three inside the pond and one in water inlet. Drastic reduction of dissolved oxygen was observed in the pond, down to 0.87 mg/L. No significant differences (P > 0.05) were observed for total CO 2, nitrite and ammonia with respect to inlet water (P1) and inside the pond (P2, P3 e P4). Chlorophyll a displayed an inverse relationship with phosphorus. Among nitrogen compounds, ammonia presented the highest concentrations except in water inlet where nitrate was higher, 513.33 μg/l, as well as the highest conductivity values. The pH was slightly acid. The results obtained showed that the macrophyte cover promoted an adverse effect in the medium. Under control, aquatic plants might impact positively due to its capacity to reduce total phosphorus and nitrate in the water column as observed in this study.
Keywords: Aquaculture; Fishpond; Macrophytes; Water quality; ammonia; carbon dioxide; chlorophyll a; dissolved oxygen; nitrite; macrophyte; nonhuman; pH; plant environment interaction; pond; temperature; water quality; water sampling